2022
DOI: 10.7759/cureus.22933
|View full text |Cite
|
Sign up to set email alerts
|

Erroneous Central Venous Catheter Placement: Multidisciplinary Primary Surgical Repair of the Vertebral Artery

Abstract: Central venous catheters are a common practice in critical care medicine. These lines are of particular importance when a patient needs large volume resuscitation or medications that cannot be infused through a peripheral line. Even though central venous catheters are frequently utilized, they are associated with potentially significant risks that one must be aware of when attempting placement. The anatomy and pertinent complications are key for any healthcare professional to be aware of during this procedure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Generally, treating arterial injury during CVC placement can be classified into three approaches: catheter removal and direct pressure, open surgery, and endovascular treatment. 4 , 5 , 6 , 7 , 8 , 9 Anatomically, the VA can be divided into four segments (V1-V4). 10 A previous study reported that the V1 segment had a predilection for injury, followed by the V2 segment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, treating arterial injury during CVC placement can be classified into three approaches: catheter removal and direct pressure, open surgery, and endovascular treatment. 4 , 5 , 6 , 7 , 8 , 9 Anatomically, the VA can be divided into four segments (V1-V4). 10 A previous study reported that the V1 segment had a predilection for injury, followed by the V2 segment.…”
Section: Discussionmentioning
confidence: 99%
“…11 In cases of arteriovenous fistulas, endovascular techniques have been preferred for treatment in recent years. 4 , 5 , 6 , 7 , 8 , 9 However, surgical excision of aneurysms remains the mainstay of treatment. 4 , 11 In our patient, injury to the V1 to V2 segment of the left VA was suspected and was expected to be difficult to compress directly.…”
Section: Discussionmentioning
confidence: 99%